2022
DOI: 10.3390/ijms23095145
|View full text |Cite
|
Sign up to set email alerts
|

On Collective Molecular Dynamics in Biological Systems: A Review of Our Experimental Observations and Theoretical Modeling

Abstract: We review processes by which different sounds, such as meditation music, mantra, kindness, or hatred expressions, and noises induce responses from cells and their components. We define ‘good’ or ‘bad’ sounds as those enhancing or inhibiting the cell’s biological activity, respectively. It is highlighted that the cellular dynamics results in a coherent organization with the formation of ordered patterns due to long-range correlations among the system constituents. Due to coherence, in the framework of quantum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Data collected in vivo and in vitro show that sound vibrations can influence the growth, structure, and behavior of cells [72][73][74]. This suggests that psychic activity and its language can determine biochemical changes (and vice versa), and therefore have a biological impact on specific diseases and therapies [72][73][74], confirming the connection between neuronal activity and somatic, phonetic, perceptive, and emotional activity [75]. Acoustic and electromagnetic waves, such as those of the heart-brain axis, can determine the dynamics and structure of cells and their components.…”
Section: Further Discussion and Concluding Remarksmentioning
confidence: 99%
“…Data collected in vivo and in vitro show that sound vibrations can influence the growth, structure, and behavior of cells [72][73][74]. This suggests that psychic activity and its language can determine biochemical changes (and vice versa), and therefore have a biological impact on specific diseases and therapies [72][73][74], confirming the connection between neuronal activity and somatic, phonetic, perceptive, and emotional activity [75]. Acoustic and electromagnetic waves, such as those of the heart-brain axis, can determine the dynamics and structure of cells and their components.…”
Section: Further Discussion and Concluding Remarksmentioning
confidence: 99%
“…In the literature, taking into account fractal structure, a large number of experimental and theoretical studies have been suggested to investigate the various physical properties of matter by the exploration of fractality. [ 26–32 ] Based on fractal geometry, an efficient new modified Debye approach has been advanced for accurately predicting the heat capacities of substances. [ 33–38 ] Especially in ref.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24–26 ] B. Mandelbrot worked on the development of fractal theory to characterize natural systems, [ 1 ] who first mentioned such representations suitable for describing complex structures. [ 24–32 ] The fractal structure approximation is a very effective model for describing natural substances on all dimensions. In the literature, taking into account fractal structure, a large number of experimental and theoretical studies have been suggested to investigate the various physical properties of matter by the exploration of fractality.…”
Section: Introductionmentioning
confidence: 99%